2014
DOI: 10.1186/1471-230x-14-152
|View full text |Cite
|
Sign up to set email alerts
|

A second-look endoscopy may not reduce the bleeding after endoscopic submucosal dissection for gastric epithelial neoplasm

Abstract: BackgroundGastric endoscopic submucosal dissection (ESD) has gradually come to be recommended as the optimal treatment for early gastric cancer; however, one of the primary issues is postoperative bleeding. Although second-look endoscopy is conventionally performed to reduce the risk of postoperative bleeding, its benefit has not yet been clearly elucidated. The objective of this study was to elucidate the benefit of second-look endoscopy.MethodsA total of 459 lesions in patients were underwent gastric ESD fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 34 publications
0
33
1
Order By: Relevance
“…25 Other clinical factors were analyzed in a few studies. Helicobacter pylori infection, 13,14,22 body mass index, 22,29,36 hyperlipidemia, 24,29,31,34,42 hyperuricemia, 36 pulmonary disease, 34 history of peptic ulcer, 31 hemoglobin level, 22 prothrombin, and activated partial thromboplastin time 22,25 were not found to be associated with PPB. Thrombocytopenia was associated with PPB in 1 study, 43 although 2 studies did not find differences in PPB rates.…”
Section: Risk Factors For Ppbmentioning
confidence: 90%
See 4 more Smart Citations
“…25 Other clinical factors were analyzed in a few studies. Helicobacter pylori infection, 13,14,22 body mass index, 22,29,36 hyperlipidemia, 24,29,31,34,42 hyperuricemia, 36 pulmonary disease, 34 history of peptic ulcer, 31 hemoglobin level, 22 prothrombin, and activated partial thromboplastin time 22,25 were not found to be associated with PPB. Thrombocytopenia was associated with PPB in 1 study, 43 although 2 studies did not find differences in PPB rates.…”
Section: Risk Factors For Ppbmentioning
confidence: 90%
“…36 Similarly, diabetes mellitus was not identified as a significant risk factor in any study. [13][14][15][16][17][18][20][21][22][23][24][28][29][30][31]33,34,36,42,44,45 Cardiopathy (ischemic heart disease in most studies), 10 were not identified as risk factors for PPB in most studies. Chronic kidney disease was not identified as a risk factor in some studies despite a trend to higher bleeding.…”
Section: Risk Factors For Ppbmentioning
confidence: 95%
See 3 more Smart Citations